2013
DOI: 10.17705/1cais.03304
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Moderating Role of Gender in Arabian Workers’ Acceptance of Computer Technology

Abstract: Even as information technology becomes globally ubiquitous, the pace of its dissemination varies across regions. For example, technology acceptance by ordinary workers in the Arabian region is generally slow, though its diffusion has recently exhibited substantial improvements. The research model proposed herein, based in the theory of planned behavior and the technology acceptance model, focuses on the effects of gender, because long-standing Saudi Arabian culture traditions and entrenched social norms define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
0
1
0
Order By: Relevance
“…Venkatesh and Davis (2000) found that when a person's co-workers perceived a system to be useful, that individual tended to share the same view. A series of recent studies (e.g., Azam and Lubna 2013;Hopp 2013;Hu et al 2013;Teo and Zhou 2014;Zolait 2014) have provided empirical support for this. Therefore, the following hypotheses were proposed:…”
Section: Attitudes Toward Use (Atu)mentioning
confidence: 93%
“…Venkatesh and Davis (2000) found that when a person's co-workers perceived a system to be useful, that individual tended to share the same view. A series of recent studies (e.g., Azam and Lubna 2013;Hopp 2013;Hu et al 2013;Teo and Zhou 2014;Zolait 2014) have provided empirical support for this. Therefore, the following hypotheses were proposed:…”
Section: Attitudes Toward Use (Atu)mentioning
confidence: 93%
“…From this data, it is known that the identity of respondents is dominated by employees who are female (71.7%). This means that most of the employees related to the use of SIMRS are women where in their use, women are influenced by the convenience factor Source: Processed Primary Data [11]. Meanwhile, the convenience factor in the use of technology can increase a person's confidence to facilitate all efforts [12].…”
Section: Characteristics Of Respondentsmentioning
confidence: 99%